Subak Endurance in Facing External Development in South Bali, Indonesia - Sriartha, I Putu; Giyarsih, Sri Rum (International Research Journal of Management, IT & Social Sciences, 2017)
Traditional Balinese irrigation system is managed by the traditional institution called subak. UNESCO has established subak as world cultural heritage that must be protected. The facts on the field showed the existence of subak is increasing threatened along with its external environment development...